Changing Traditions and Village Development in Kalotaszentkirály - Wayne, Kraft (Center for Studies in Oral Tradition, 2018)
The continuity of village traditions depends on the stability and cohesion of village communities. Since the opening of Transylvania after the fall of Nicolae Ceauşescu, there has been a sort of revival of Hungarian village dance and music, on the one hand, but, on the longer term, the communities themselves are threatened by economic challenges and by consequent demographic changes. This essay is based on field research conducted in Kalotaszentkirály (Sincraiu) from 1995 to 2010.